2022
DOI: 10.1177/15459683221110884
|View full text |Cite
|
Sign up to set email alerts
|

The Reaching Phase of Feeding and Self-Care Actions Optimizes Action Observation Effects in Chronic Stroke Subjects

Abstract: Background The Action Observation Therapy (AOT) is a well-established post-stroke rehabilitation treatment based on the theoretical framework of the Mirror Neuron System (MNS) activation. However, AOT protocols are still heterogeneous in terms of video contents of observed actions. Objective The aim of this study was to analyze electroencephalographic (EEG) recordings in stroke patients during the observation of different videos of task-specific upper limb movements, and to define which category of actions can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…EEG signals were recorded in 20 patients with stroke in chronic stage during the observation of task-oriented upper limb tasks (including self-care and feeding actions) and nonfinalized actions. The comparison of EEG rhythms between the 2 groups of motor actions (ie, task-oriented and non-task-oriented) revealed that an increased suppression of mu and beta bands occurred during the observation of the former category [37].…”
Section: Introductionmentioning
confidence: 99%
“…EEG signals were recorded in 20 patients with stroke in chronic stage during the observation of task-oriented upper limb tasks (including self-care and feeding actions) and nonfinalized actions. The comparison of EEG rhythms between the 2 groups of motor actions (ie, task-oriented and non-task-oriented) revealed that an increased suppression of mu and beta bands occurred during the observation of the former category [37].…”
Section: Introductionmentioning
confidence: 99%